Making 'Modern Fairies': Making Fairies Modern. Issue 1 (2nd January 2021) - Larrington, Carolyne; Hield, Fay
Abstract: The Arts and Humanities Research Council-funded project 'Modern Fairies and Loathly Ladies' investigated what happened when a number of artists (musicians, writers, filmmakers) were asked to respond to and re-mediate a curated selection of traditional stories about fairies and loathly ladies. The artists came to the project with a spectrum of different views about fairies, ranging from belief in their existence to absolute scepticism about the supernatural. The works-in-progress they created were performed in a series of experimental shows at The Sage Gateshead theatre in 2019. The artists took up certain themes such as the otherworld, time slippage, fairies, and children, but were not attracted by others. Fairy material was reconfigured to reflect contemporary concerns about the natural world and to explore ways in which magical human–animal transformation spoke to women's experience.